Experimental studies on electrostatic removal of particulate matter emission from diesel engine using active reduction technique - Mohankumar Subramanian; Senthilkumar Pachamuthu; Jenoris Muthiya Solomon; Beena Stanislaus Arputharaj; Pradesh Sakthivel; Arunkumar Karuppasamy; Subhav Singh; Deekshant Varshney; Vijayanandh Raja (Results in Engineering, 2025)
Particulate matter (PM) emission is considered as a key pollutant from diesel engines and needs to be controlled properly. It is harmful to human health and vitiates atmospheric visibility. The primary particulate matter control technique now used in diesel engine is the diesel particulate filter (DPF). Although DPF shows high filtration efficiency, it has several drawbacks which include high back pressure, more fuel consumption, more operating cost, low thermal resistance and reduced life. In this work, a model of Electrostatic precipitators (ESP) was developed, and various governing parameters were studied in order to facilitate better particulate collection. The basic working of ESP is that it only exerts an force electrostatically on the particle and this force is used to trap the particulate to the ESP plates and this will result in a comparatively lower pressure drop and less operating cost. The various parameters like diameter of discharge electrode, collection electrodes numbers, operating temperature and applied voltage were varied, and the corresponding trapping efficiency of ESP was explored. Test results obtained showed that ESP with minimum discharge electrode diameter (3 mm), the maximum number of collection plates and higher applied voltage (20 kV) could give a higher collection efficiency of around 95 %. Regarding other emissions, slight declination in HC and NOx emission observed at higher applied voltage conditions. Particle size filtration efficiency revealed that the designed ESP showed greater filtration efficiency for particles having sizes greater than 3 µm.